Migration in Uzbekistan: Threat or Opportunity? Analyzing social and economic impacts of migration in changing society - Baydarova Sabina Baxtiyarovna,; Abdullayeva Iroda Makhmudjanovna, (NAZARIY VA AMALIY FANLARDAGI USTUVOR ISLOHOTLAR VA ZAMONAVIY TA'LIMNING INNOVATSION YO'NALISHLARI, 2025)
This paper explores the complex role of migration in Uzbekistan’s current social and economic context. It discusses how migration can bring positive outcomes—such as remittances, professional growth abroad, and the return of skilled workers—while also raising concerns like brain drain, labor market pressure, and infrastructure strain. Based on recent data and policy directions, the paper suggests that with a more balanced and targeted migration policy, Uzbekistan can reduce associated risks and use migration as a tool for sustainable development.